Effects of Axial Ligands on the Photosensitising Properties of Silicon Octaphenoxyphthalocyanines - Maree, Machiel David (Rhodes University, Faculty of Science, Department of Chemistry, 2002)
Various axially substituted Silicon octaphenoxyphthalocyanines were synthesised as potential photosensitisers in the photodynamic therapy of cancer. Conventional reflux reactions were used for synthesis as well as new microwave irradiation reactions, wherein the reaction times were decreased tenfold with a marginal increase in reaction yield and product purity. An interesting series of oligomeric (dimer to a nonamer) silicon octaphenoxyphthalocyanines were also successfully synthesised in a reaction similar to polymerisation reactions. These compounds were found to undergo an axial ligand transformation upon irradiation with red light (> 600 nm) in dimethylsulphoxide solution. All the ligands were transformed into the dihydroxy silicon octaphenoxyphthalocyanine with varying degrees of phototransformation quantum yields ranging in order from 10â »Â³ to 10â »â µ depending on the axial ligand involved. During and after axial ligand transformations a photodegredation of the dihydroxy silicon octaphenoxy phthalocyanine was observed upon continued irradiation. The oligomers were found to undergo the same axial ligand transformation process with a phototransformation quantum yield of 10â »â µ The singlet oxygen quantum yields of the unaggregated monomeric silicon octaphenoxy phthalocyanines were all found to be approximately 0.2 with the exception of a compound with two (trihexyl)siloxy axial substituents that had a singlet oxygen quantum yield of approximately 0.4 in dimethylsulphoxide solutions. The oligomers showed a surprising trend of an increase in singlet oxygen quantum yield with an increase in phthalocyanine ring number up to the pentamer and then a dramatic decrease to the nonamer. The triplet quantum yield and triplet lifetime were determined by laser flash photolysis for selected compounds and no correlation was observed with any of these properties and the singlet oxygen quantum yields. These selected compounds all fluoresce and a very good correlation was found between the fluorescence lifetimes determined experimentally by laser photolysis and the Strickler-Berg equation for the non-aggregated compounds. Electrochemical measurements also indicate the importance of the axial ligands upon the behaviour of the phthalocyanines as cyclic voltammetric behaviour was determined by the nature of the axial ligand.
Keywords: Ligands; Photochemotherapy; Phthalocyanines